The Polyphenol Pterostilbene Ameliorates the Myopathic Phenotype of Collagen VI Deficient Mice via Autophagy Induction - Metti, Samuele; Gambarotto, Lisa; Chrisam, Martina; Spina, Martina La; Baraldo, Martina; Braghetta, Paola; Blaauw, Bert; Bonaldo, Paolo (Frontiers in Cell and Developmental Biology, 2020)
The induction of autophagy, the catabolic pathway by which damaged or unnecessary cellular components are subjected to lysosome-mediated degradation and recycling, is impaired in Collagen VI (COL6) null mice and in COL6-related myopathies. This autophagic impairment causes an accumulation of dysfunctional mitochondria, which in turn leads to myofiber degeneration. Our previous work showed that reactivation of autophagy in COL6-related myopathies is beneficial for muscle structure and function both in the animal model and in patients. Here we show that pterostilbene (Pt) – a non-toxic polyphenol, chemically similar to resveratrol but with higher bioavailability and metabolic stability – strongly promotes in vivo autophagic flux in the skeletal muscle of both wild-type and COL6 null mice. Reactivation of autophagy in COL6-deficient muscles was also paralleled by several beneficial effects, including significantly decreased incidence of spontaneous apoptosis, recovery of ultrastructural defects and muscle remodeling. These findings point at Pt as an effective autophagy-inducing nutraceutical for skeletal muscle with great potential in counteracting the major pathogenic hallmarks of COL6-related myopathies, a valuable feature that may be also beneficial in other muscle pathologies characterized by defective regulation of the autophagic machinery.